Environmental & architectural phenomenology. Vol. 2, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 1991)
Vol. 2, No. 2, Spring 1991 (includes "citations received,” poems by Miles Richardson & Jill Yesko, and essay by Mark Lappan).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals